Genome-wide comparative analysis of RNA-binding Glycine-rich protein family genes between Gossypium arboreum and Gossypium raimondii. - Wencui Yang; Min Yu; Changsong Zou; Cairui Lu; Daoqian Yu; Hailiang Cheng; Pengfei Jiang; Xiaoxu Feng; Youping Zhang; Qiaolian Wang; Hong Zhang; Guoli Song; et al. (PLoS ONE, 2019)
RB-GRP (RNA-binding Glycine-rich protein gene) family belongs to the fourth subfamily of the GRP (Glycine-rich protein gene) superfamily, which plays a great role in plant growth and development, as well as in abiotic stresses response, while it has not been identified in cotton. Here, we identified 37 and 32 RB-GRPs from two cotton species (Gossypium arboreum and Gossypium raimondii, respectively), which were divided into four distinct subfamilies based on the presence of additional motifs and the arrangement of the glycine repeats. The distribution of RB-GRPs was nonrandom and uneven among the chromosomes both in two cotton species. The expansion of RB-GRP gene family between two cultivars was mainly attributed to segmental and tandem duplication events indicated by synteny analysis, and the tandem duplicated genes were mapped into homologous collinear blocks, indicated that they shared a common ancestral gene in both species. Furthermore, most RB-GRPs in two cotton species undergone stronger negative selective pressure by evolutionary analysis of RB-GRP orthologous genes. Meanwhile, RB-GRPs participated in different abiotic stresses (Abscisic acid, salt and Polyethylene glycol) responses and tissues at different developmental stages between two cotton species were showed by gene expression analysis. This research would provide insight into the evolution and function of the RB-GRPs in Gossypium species.